Linking the Diversity of Yeasts Inherent in Starter Cultures to Quorum Sensing Mechanism in Ethnic Fermented Alcoholic Beverages of Northeast India - Nath, Bhaskar Jyoti; Parasar, Deep Prakash; Sarma, Hridip Kumar (Frontiers in Sustainable Food Systems, 2021)
In this review, the relevance of diversity of yeasts and their interactive association in household ethnic fermentation are discussed. The longstanding traditional household fermentation practice involves preparation of fermented product such as alcoholic beverages from various indigenous agricultural products with the help of microorganisms cultivated from local environment and perpetuated for hundreds of years through generations indoctrinating an indigenous knowledge system. Northeast India is known for its rich physiographic and geo-demographic diversity and is home to several ethnicities who follow unique practices of household traditional fermentation. The diversity of yeasts present within the microbial inoculum used for fermentation by different indigenous communities has been keenly studied and reported to be unique in spite of their common source for starter substrates. Saccharomyces yeasts are primarily involved in alcoholic fermentation, whereas non-Saccharomyces yeasts, which are reportedly confined to a particular geographical region, have been reported to contribute toward the final outcome of fermentation produce. During fermentation, interaction among these large microbial communities and their resulting physiological expression within the fermentation micro-environment is believed to affect the final quality of the product. Mechanism of quorum sensing plays an important role in these interactions in order to maintain proportionality of different yeast populations wherein the quorum sensing molecules not only regulate population density but also effectively aid in enhancement of alcoholic fermentation. Additionally, various secondary metabolites, which are secreted as a result of inter-species interactions, have been found to affect the quality of beverages produced. This review concludes that diverse species of yeasts and their interaction within the fermentation micro-environment influence the sustainability and productivity of household ethnic fermentation.